2023
DOI: 10.21037/tp-23-111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the efficacy of Dabuyin pill combined with gonadotropin-releasing hormone analogue in the treatment of central precocious puberty girls based on network pharmacology

Abstract: Background: Traditional Chinese medicine (TCM) believes that central precocious puberty (CPP) is affected by the imbalance of kidney Yin and Yang. Dabuyin pill is a recipe for nourishing Yin and lowering fire. The network pharmacology method was used to analyze the active components, action targets, and molecular pathways of Dabuyin pill in the treatment of CPP. Methods: The main chemical components of Dabuyin pill were obtained from the Integrative database of Traditional Chinese Medicine enhanced by Symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Zhou et al found that phthalate exposure is associated with an increased incidence of precocious puberty in girls in a case-control study, and Shao et al found that Di-(2-ethylhexyl) phthalate (DEHP) induces precocious puberty in female rats by upregulating the IGF-1/PI3K/Akt/mTOR signaling pathway (15). Several studies have also pointed out (including a RCT study) that the PI3K/Akt signaling pathway or Akt1 is a key target for the prevention or treatment of precocious puberty (36)(37)(38)(39)(40). However, no significant causality between Akt levels in plasma and CPP was found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al found that phthalate exposure is associated with an increased incidence of precocious puberty in girls in a case-control study, and Shao et al found that Di-(2-ethylhexyl) phthalate (DEHP) induces precocious puberty in female rats by upregulating the IGF-1/PI3K/Akt/mTOR signaling pathway (15). Several studies have also pointed out (including a RCT study) that the PI3K/Akt signaling pathway or Akt1 is a key target for the prevention or treatment of precocious puberty (36)(37)(38)(39)(40). However, no significant causality between Akt levels in plasma and CPP was found in our study.…”
Section: Discussionmentioning
confidence: 99%